1989
DOI: 10.1007/bf00210673
|View full text |Cite
|
Sign up to set email alerts
|

Isochromosome not translocation in trisomy 21q21q

Abstract: After primary trisomy, "de novo" 21q21q trisomy is the most frequent chromosomal aberration responsible for Down syndrome. This rearrangement is more commonly referred to as a Robertsonian translocation or centric fusion product than as an isochromosome, e.g., t(21q;21q) instead of i(21q); however, in practice, it has not so far proved possible to distinguish between these alternatives. The aim of this work was to establish which of the two alternatives is acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 5 publications
3
27
2
Order By: Relevance
“…The origin of the trisomy has been determined in a total of 7 t(13;13) trisomy 13 cases using molecular polymorphisms, four of which have been maternal and three paternal in origin [present study (2 cases); Hassold et al, 1987 (1 case); Shaffer et al, 1994 (4 cases)]. Similarly, studies on the origin of t(21;21) chromosomes ascertained through trisomy 21 indicate that these are usually isochromosomes, and an approximately equal ratio of maternally to paternally derived cases was found [Grasso et al, 1989;Antonarakis et al, 1990;Shaffer e t al., 1991, 19931. Most isochromosomes have shown no evidence of recombination, consistent with a postmeiotic origin.…”
Section: Resultssupporting
confidence: 54%
“…The origin of the trisomy has been determined in a total of 7 t(13;13) trisomy 13 cases using molecular polymorphisms, four of which have been maternal and three paternal in origin [present study (2 cases); Hassold et al, 1987 (1 case); Shaffer et al, 1994 (4 cases)]. Similarly, studies on the origin of t(21;21) chromosomes ascertained through trisomy 21 indicate that these are usually isochromosomes, and an approximately equal ratio of maternally to paternally derived cases was found [Grasso et al, 1989;Antonarakis et al, 1990;Shaffer e t al., 1991, 19931. Most isochromosomes have shown no evidence of recombination, consistent with a postmeiotic origin.…”
Section: Resultssupporting
confidence: 54%
“…The syndromic effects in those cases were probably due to UPD rather than deletion-based, as has been shown in a recent case of Angelman syndrome with t( 15;15) [Malcolm et al, 19911. This likelihood of isodisomy in these cases is enhanced by evidence that most homologous 21;21 Robertsonian translocations in Down syndrome are true molecular isochromosomes [Antonarakis et al, 1990;Grasso et al, 1989;Shaffer et al, 19921. Thus, balanced homologous Robertsonian translocation carriers appear t o be a good source for cases of UPD, although 14;14 carriers are the least common [Therman et al, 19891.…”
Section: Discussionmentioning
confidence: 96%
“…On the cytogenetic level, it was not possible to distinguish an isochromosome i(13q) from a Robertsonian translocation of two homologous chromosomes 13. DNA studies of trisomy 21 due to de novo rea(21q;21q) have concluded that the majority is due to isochromosomes i(21q) and not translocations between two chromosomes 21 [14][15][16][17]. Similar [18][19][20][21].…”
Section: Discussionmentioning
confidence: 94%
“…Robertsonian translocations are the most common human structural chromosomal abnormalities with an incidence of 1.23/ 1000 live births [5,6]. They are mainly observed in group D chromosomes (i.e., 13,14,15) and group G (i.e., 21 and 22). The D/D translocation is the most frequent type, with a high predominance of 13;14 translocations [6,7].…”
Section: Introductionmentioning
confidence: 99%